PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA - Maemunah Fadillah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Metro, 2022)
ABSTRACT The lack of variety of learning methods used by teachers in delivering learning, results in students being passive and less actively involved in learning activities in class. Therefor, it is important for teachers to have the right strategy to overcome the learning difficulties faced by students. One method that can be used to stimulate students to think creatively is to use the mind mapping method. The purpose of this research is to find out is there any effect of using mind mapping methods on social studies learning outcomes for students in junior high schools. This type of research is experimental research. The population in this study were all students of class VIII and the samples were students of class VIII A and VIII B which were selected through purposive sampling technique. Data collection instruments include tests and questionnaires. Analysis of the data used is the percentage test, normality test, homogenity test, NGain test, independent sample t-test. The results of the study were based on the analysis of the final data t-test test were obtained a sig (2-tailed) value of 0.027 < 0.05. Because a sig (2-tailed) value < of 0.05 means Ho is rejected and Ha is accepted. This means that there is an influence on the use of mind mapping methods on students' IPS learning outcomes.